Interval Running vs Steady-State Jogging Training: A Case Study of Fat Percent Reduction - Nurhalisa Nurhalisa; Nurul Sukmawati R (Universitas Pejuang Republik Indonesia, 2025)
Background: Body fat percentage reduction is one of the primary objectives among recreational runners, and various training modalities have been proposed to achieve this outcome efficiently. Interval running training and steady-state jogging represent two widely practiced approaches with distinct physiological demands, yet comparative evidence regarding their relative effectiveness in reducing body fat percentage among recreational running club members remains limited. Objectives: This study aimed to compare the effect of interval running training and steady-state jogging on body fat percentage reduction among members of a recreational running community. Methods: This study employed a quantitative approach using a Quasi-Experimental Two-Group Pretest-Posttest Design. The participants consisted of 40 members of a recreational running club selected through purposive sampling and divided into two groups: an interval training group (n = 20) and a steady-state jogging group (n = 20). The intervention was conducted over eight weeks with a frequency of three sessions per week. The interval training group performed repeated high-intensity running bouts alternated with active recovery periods, while the steady-state jogging group performed continuous running at a constant moderate intensity for an equivalent total duration. Body fat percentage was measured using bioelectrical impedance analysis (BIA), and VO2max was estimated using the Multistage Fitness Test (Bleep Test). Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, Paired Sample t-Test, and Independent Sample t-Test at a significance level of α = 0.05. Results: Both groups demonstrated significant reductions in body fat percentage following the intervention. The interval training group showed a decrease from 26.84 ± 4.12% to 21.37 ± 3.58%, representing a 20.38% reduction (p = 0.000), while the steady-state jogging group showed a decrease from 27.05 ± 4.46% to 23.92 ± 4.01%, representing an 11.58% reduction (p = 0.000). The independent sample t-test revealed a significantly greater reduction in the interval training group compared to the steady-state jogging group (p = 0.002). Conclusions: Interval running training produces a significantly greater reduction in body fat percentage compared to steady-state jogging among recreational running club members, suggesting that interval training is a more time-efficient and metabolically effective strategy for body composition improvement in this population.